The novel μ‐opioid receptor agonist PZM21 depresses respiration and induces tolerance to antinociception. (14th May 2018) - Hill, Rob; Disney, Alex; Conibear, Alex; Sutcliffe, Katy; Dewey, William; Husbands, Stephen; Bailey, Chris; Kelly, Eamonn; Henderson, Graeme
Abstract : Background and Purpose: PZM21 is a novel μ‐opioid receptor ligand that has been reported to induce minimal arrestin recruitment and be devoid of the respiratory depressant effects characteristic of classical μ receptor ligands such as morphine. We have re‐examined the signalling profile of PZM21 and its ability to depress respiration. Experimental Approach: G protein (Gi ) activation and arrestin‐3 translocation were measured in vitro, using BRET assays, in HEK 293 cells expressing μ receptors. Respiration (rate and tidal volume) was measured in awake, freely moving mice by whole‐body plethysmography, and antinociception was measured by the hot plate test. Key Results: PZM21 (10 −9 – 3 × 10 −5  M) produced concentration‐dependent Gi activation and arrestin‐3 translocation. Comparison with responses evoked by morphine and DAMGO revealed that PZM21 was a low efficacy agonist in both signalling assays. PZM21 (10–80 mg·kg −1 ) depressed respiration in a dose‐dependent manner. The respiratory depression was due to a decrease in the rate of breathing not a decrease in tidal volume. On repeated daily administration of PZM21 (twice daily doses of 40 mg·kg −1 ), complete tolerance developed to the antinociceptive effect of PZM21 over 3 days but no tolerance developed to its respiratory depressant effect. Conclusion and Implications: These data demonstrate that PZM21 is a low efficacy μ receptor agonist for both G protein and arrestin signalling. Contrary to a previous report, PZM21 depresses respiration in a manner similar to morphine, the classical opioid receptor agonist.